SERPINI1 pathogenic variants: An emerging cause of childhood‐onset progressive myoclonic epilepsy. Issue 9 (20th June 2017) - Ranza, Emmanuelle; Garcia‐Tarodo, Stephanie; Varvagiannis, Konstantinos; Guipponi, Michel; Lobrinus, Johannes A.; Bottani, Armand; Kern, Ilse; Kurian, Mary; Pittet, Marie‐Pascale; Antonarakis, Stylianos E.; Fluss, Joel; Korff, Christian M.
Abstract : Progressive myoclonic epilepsies are rare neurodegenerative diseases with a wide spectrum of clinical presentations and genetic heterogeneity that render their diagnosis perplexing. Discovering new imputable genes has been an ongoing process in recent years. We present two pediatric cases of progressive myoclonic epilepsy with SERPINI1 pathogenic variants that lead to a severe presentation; we highlight the importance of including this gene, previously known as causing an adult‐onset dementia‐epilepsy syndrome, in the genetic work‐up of childhood‐onset progressive myoclonic epilepsies.